LGBTQI+ in democratic Portugal: An overview essay - Vale de Almeida, M. (Portuguese Journal of Social Science, 2021)
Written in a reflexive, autoethnographic and essayistic mode, this article aims to provide an overview of the developments of LGBTQI+ rights in democratic Portugal and to identify the main frictions that affected and continue to affect them, while also providing glimpses of possible routes – in broad strokes – for making effective the changes in the life politics of LGBTQI+ people that are guaranteed in law.